Phenotypic Characterization of Youth Admitted To Acute Psychiatric Inpatient Unit Following Self-Harm Behavior. Issue 3 (3rd July 2022) - Schwartz-Lifshitz, Maya; Ben-Dor, David H.; Bustan, Yael; Zalsman, Gil; Gothelf, Doron; Weizman, Abraham; Barzilay, Ran
Abstract: Objective: Deliberate self-harm (DSH) is a major health concern among adolescents, and is often associated with the need for inpatient psychiatric hospitalization. The aim of this study was to identify clinical and demographic characteristics associated with DSH behavior among adolescents admitted to an acute psychiatric inpatient unit. Method: We retrospectively analyzed data from the electronic medical records of consecutive admittances to a single acute adolescent inpatient unit ( n  = 703, mean age 15.2). We compared inpatients with DSH to inpatients without DSH and further compared within the DSH group based on the presence of suicidal intent. Results: Compared to Non-DSH inpatients ( n  = 497), youths admitted following DSH ( n  = 206) were more likely to be female (OR = 2.6, 95%CI 1.7–4), currently in depressive exacerbation (OR = 2.4, 95%CI 1.6–3.6), with concurrent suicidal ideation (OR = 3.9, 95%CI 2.5–5.9), and history of alcohol use (OR = 5.6, 95%CI 3.2–9.5). Within DSH youths, no significant clinical differences were identified between those admitted following a suicide attempt ( n  = 102) compared to non-suicidal-self-injury ( n  = 104), who were generally younger. Conclusions: Findings suggest that early detection and intervention of DSH and depressive crisis is warranted, regardless of the self-harm subtype. HIGHLIGHTS: Deliberate self-harm is common among adolescent psychiatric inpatients. Adolescent inpatients with deliberate self-harm are predominantly females with concurrent depression and suicidal ideation. We did not detect significant clinical and demographic differences between self-harmers with or without suicidal intent.